A functional role of NMDA receptor in regulating the differentiation of oligodendrocyte precursor cells and remyelination. Issue 5 (26th February 2013) - Li, Cui; Xiao, Lin; Liu, Xiuyun; Yang, Wenjing; Shen, Weiran; Hu, Chun; Yang, Guang; He, Cheng
<x xml:space="preserve">Abstract</x> Differentiation of oligodendrocyte precursor cells (OPCs) is the most important event for the myelination of central nervous system (CNS) axons during development and remyelination in demyelinating diseases, while the underlying molecular mechanisms remain largely unknown. Here we show that NMDA receptor (NMDAR) is a functional regulator of OPCs differentiation and remyelination. First, GluN1, GluN2A, and GluN2B subunits are expressed in oligodendrocyte lineage cells (OLs) in vitro and in vivo by immunostaining and Western blot analysis. Second, in a purified rat OPC culture system, NMDARs specially mediate OPCs differentiation by enhancing myelin proteins expression and the processes branching at the immature to mature oligodendrocyte transition analyzed by a serial of developmental stage‐specific antigens. Moreover, pharmacological NMDAR antagonists or specific knockdown of GluN1 by RNA interference in OPCs prevents the differentiation induced by NMDA. NMDA can activate the mammalian target of rapamycin (mTOR) signal in OPCs and the pro‐differentiation effect of NMDA is obstructed by the mTOR inhibitor rapamycin, suggesting NMDAR exerts its effect through mTOR‐dependent mechanism. Furthermore, NMDA increases numbers of myelin segments in DRG‐OPC cocultures. Finally, NMDAR specific antagonist MK801 delays remyelination in the cuprizone model examined by LFB‐PAS, immunofluorescence and electron microscopy. This effect appears to result from inhibiting OPCs differentiation as more NG2+ OPCs but less GST‐π+ mature oligodendrocytes are observed. Together, these results indicate that NMDAR plays a critical role in the regulation of OPCs differentiation in vitro and remyelination in cuprizone model which may provide potential target for the treatment of demyelination disease.